Effects of strength training on body composition in young male professional soccer players - Suarez-Arrones, L.; Lara-Lopez, P.; Torreno, N.; Saez de Villarreal, E.; Di Salvo, V.; Mendez-Villanueva, A. (Sports, 2019)
The present prospective cohort study investigated changes in body composition (BC) in young male football players (n = 18, 16.1 ± 0.8 years; 181.0 ± 0.1 cm; 71.3 ± 4.9 kg) after combined football and strength training (ST) during a whole in-season period (26 weeks). BC was measured at whole-body absolute and regional levels by dual-energy X-ray absorptiometry in eighteen players at the beginning and at the end of the competitive period. The ST was organized into three different session types: ST in the gym, specific ST on the field, and individual ST (weak points). The results of the present study indicated that fat-free mass (FFM) was substantially higher following the competitive period (5.1% ± 1.2%), while percentage of fat showed no changes during the competitive period. At the regional level, arms` and legs` FFM increased at the end of the season, and bone mineral content (BMC) and density (BMD) increased in arms, legs, pelvis, thoracic spine, and lumbar spine. In conclusion, within the limitation of the potential positive impact of growth and/or maturation, present results seem to indicate that an ST program that supplements football-related training sessions could be an effective option to increase FFM, BMC, and BMD at both whole-body and regional level across the competitive season in young male professional football players.